Barriers and facilitators to medicine collection through the CCMDD programme at a Durban Hospital - Simangele I. Hlongwana; Andrew L. Gray (AOSIS, 2022)
Background: South Africa has rekindled health reform efforts through the implementation of the Centralised Chronic Medicine Dispensing and Distribution (CCMDD) programme, as a precursor towards achieving envisioned National Health Insurance (NHI). The CCMDD programme enables stable patients to collect chronic medicines dispensed centrally from designated pick-up-points (PuPs). Barriers and facilitators of chronic medicine collection exist at different levels. Aim: To identify barriers and facilitators associated with patients' characteristics and noncollection of CCMDD patient medicine parcels (PMPs). Setting: The study was conducted at a regional public sector hospital which provides support for 19 primary facilities. Methods: An observational cross-sectional comparative study was conducted. Results: There was no statistically significant difference in collection status in terms of most of the variables compared. Patients who had been on treatment longer or who were receiving multiple items were more likely to collect medication, as were patients with arthritis, HIV and AIDS, but the association was no longer significant after adjusting for other confounders. Patients using internal PuPs were significantly more likely to collect their PMPs than patients using external PuPs, and this may have implications for achieving CCMDD objectives. Conclusion: This study has revealed that recently diagnosed patients are enrolled onto the CCMDD programme whilst the chronic condition stability is not yet attained. Patients were also enrolled onto the programme at the referral facility instead of being down-referred. Contribution: This study makes a case for evaluation research to further assess the CCMDD programme implementation, in order to improve uptake and cost-effectiveness.